logo
In [1]:
import proveit
from proveit import A
from proveit.logic import Not
from proveit.logic.booleans  import false_not_true
theory = proveit.Theory() # the theorem's theory
In [2]:
%proving untrue_from_negation
With these allowed/disallowed theorem/theory presumptions (e.g., to avoid circular dependencies), we begin our proof of
untrue_from_negation:
(see dependencies)
untrue_from_negation may now be readily provable (assuming required theorems are usable).  Simply execute "%qed".
In [3]:
false_not_true
In [4]:
A_eq_F = Not(A).prove(assumptions=[Not(A)]).equate_negated_to_false()
A_eq_F:  ⊢  
In [5]:
A_untrue = A_eq_F.sub_left_side_into(false_not_true)
A_untrue:  ⊢  
In [6]:
%qed
proveit.logic.booleans.negation.untrue_from_negation has been proven.
Out[6]:
 step typerequirementsstatement
0generalization1  ⊢  
1instantiation2, 3, 4  ⊢  
  : , :
2theorem  ⊢  
 proveit.logic.equality.substitute_falsehood
3axiom  ⊢  
 proveit.logic.booleans.false_not_true
4assumption  ⊢